PENGARUH ASESMEN FORMATIF, GAYA BELAJAR, KURIKULUM MERDEKA, P5 TERHADAP HASIL BELAJAR DI SMKN 1 SURABAYA - Almadani S, Mohammad Daffa’; Rochmawati, Rochmawati (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Learning outcomes are not absolute in the form of values but can be in the form of changes, reasoning, discipline, skills, and so on that lead to positive changes. Understanding learning outcomes is a process to determine the value of student learning through assessment activities or measurement of learning outcomes. The high and low learning outcomes of students can be influenced by several factors, such as formative assessment, student learning style, Kurikulum merdeka, and P5. This study aims to determine whether there is an influence of formative assessment, student learning style, Kurikulum merdeka, and P5 on student learning outcomes. The research used is quantitative research. Data collection was conducted through observation, interviews, documentation, and questionnaires. Samples used in the study were 120 respondents, with a total of 51 respondents. Data processing using SPSS 26 began to test research instruments, classical assumption tests, and hypothesis tests. The results showed that 1) there is a significant influence of formative assessment, student learning style, independent curriculum, and P5 on student learning outcomes; 2) there is a significant influence of formative assessment on student learning outcomes; 3) there is a significant influence of student learning style on student learning outcomes; 4) there is a significant influence of kurikulum merdeka on student learning outcomes; and 5) there is a significant influence of P5 on student learning outcomes. Keywords: Formative Assessment, Student Learning Style, kurikulum Merdeka, P5